(untitled) (Bangladesh Journal of Medical Science, 2020)
Objective. This study aims to establish the role of insertion-deletion polymorphism of the angiotensin-converting enzyme gene in development of arterial hypertension in patients with chronic obstructive pulmonary disease. Materials and Methods: The study group consisted of 96 patients: Group 1 (25 individuals with COPD), Group 2 (23 individuals with AH), Group 3 (28 individuals with COPD and AH). The control group consisted of the 20 healthy subjects. I/D genotypes of ACE were determined by polymerase chain reaction (PCR) amplification. Plasma ACE activity was determined photometrically by a commercially available kit. Results and Discussion: The distribution of polymorphic variants of the ACE gene among COPD-only patients genotype spreading was close to the data obtained in controls. In hypertensive patients, there were fewer ID heterozygotes and more ІІ homozygotes compared to controls. In the COPD+AH category of patients, II genotype was predominant in 7.1% subjects, DD genotype was predominant in 10.0% subjects and the proportion of ID heterozygotes was 17.1% lower compared to controls. The II genotype had a positive relationship with patient age and a negative relationship with body weights and respiratory rates of COPD+AH patients. The ID genotype was associated with increased respiratory rates; however, its correlation with the duration of the disease was negative. Conclusion: The data obtained in the study allow suggesting that polymorphism of the ACE gene doesn’t relate to development of AH in patients with COPD. The highest activity of ACE was found in patients with combination of COPD and AH; maximum findings of ACE activity were seen in patients with DD genotype. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.543-551